2015
DOI: 10.1186/s40317-015-0061-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic handicaps and organizational complexity in the foraging behavior of two free-ranging penguin species

Abstract: Background:Animal movement exhibits self-similarity across a range of both spatial and temporal scales reminiscent of statistical fractals. Stressors are known to induce changes in these statistical patterns of behavior, although the direction and interpretation of such changes are not always clear. We examined whether the imposition of known hydrodynamic disruptors, bio-logging devices and flipper bands, induces changes in the temporal organization (complexity) of foraging sequences in two penguin species, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
(106 reference statements)
2
3
0
Order By: Relevance
“…We observed a strong correlation between the two DFA results at each breeding stage (incubation: r = .95, p < .001; guard: r = .98, p < .001; postguard: r = .98, p < .001). Thus, both methods converged to indicate that dive sequences from foraging little penguins are best characterized as persistent, long‐range dependent fractional Gaussian noise (Figure 3), in accordance with previous studies on penguins (Cottin et al., 2014; Le Guen et al., 2018; MacIntosh et al., 2013; Meyer et al., 2015, 2017). The observed best‐scaling regions were similar for the three stages (incubation, guard and postguard) and included the scales 2 7 –2 11 , or 128–2048 s.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We observed a strong correlation between the two DFA results at each breeding stage (incubation: r = .95, p < .001; guard: r = .98, p < .001; postguard: r = .98, p < .001). Thus, both methods converged to indicate that dive sequences from foraging little penguins are best characterized as persistent, long‐range dependent fractional Gaussian noise (Figure 3), in accordance with previous studies on penguins (Cottin et al., 2014; Le Guen et al., 2018; MacIntosh et al., 2013; Meyer et al., 2015, 2017). The observed best‐scaling regions were similar for the three stages (incubation, guard and postguard) and included the scales 2 7 –2 11 , or 128–2048 s.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have shown that dive sequences from foraging penguins are best characterized as persistent, long‐range dependent fractional Gaussian noise (Cottin et al., 2014; Le Guen et al., 2018; MacIntosh, Pelletier, Chiaradia, Kato, & Ropert‐Coudert, 2013; Meyer et al., 2017; Meyer, MacIntosh, Kato, Chiaradia, & Ropert‐Coudert, 2015). In other words, dive and postdive durations of a given length are typically followed by dive and postdive durations of a similar length, with such patterns of fluctuation between these two behavioral states persisting across a range of measurement scales.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the fractal analysis, values of α DFA were similar to those reported previously for Adélie penguins at 0.94 ± 0.005 (Meyer et al., ), indicating that foraging time series were long‐range dependent and persistent ( α DFA >0.5, i.e. dive and post‐dive times of a given length were more likely to be followed by dive and postdive times of similar lengths).…”
Section: Resultssupporting
confidence: 85%
“…() and applied to Adélie penguins in Cottin et al. () and Meyer, MacIntosh, Kato, Chiaradia, and Ropert‐Coudert (), we used Detrended Fluctuation Analysis (DFA; Peng et al., ) to measure long‐range dependence in the sequential distribution of dives and surface times as an indicator of complexity in individual diving sequences. We performed DFA using the “fractal” package (Constantine & Percival, ) in R to estimate the scaling exponents ( α DFA ) of these sequences (Peng et al., ), which measures the degree to which time series are long‐range dependent and statistically self‐similar (Taqqu, Teverovsky, & Willinger, ).…”
Section: Methodsmentioning
confidence: 99%
“…Penguins were equipped with a GPS logger (CatTrack, South Carolina, USA) recording a position every 2 -6 s, and an accelerometer data logger (G6aþ, CEFAS Technology Pty Ltd, Suffolk, UK) recording tri-axial acceleration and depth at a frequency of 30 Hz during dives greater than 1.5 m. The combined tag weight was 62 g in air, less than 6% of the mean bodyweight (1038.7 g + 8.9 in this study) and the proportional cross-sectional area was less than 3.5%, an important consideration for logger effects on penguins due to the influence of drag [25,26]. For further details regarding tag specifications and attachment protocols see Carroll et al [20,21].…”
Section: Materials and Methods (A) Penguin Trackingmentioning
confidence: 80%